Seeing Time : Selections from the Pamela and Richard Kramlich Collection of Media Art - Iles, Chrissie; Riley, Robert; Ross, David A.; Sturken, Marita; Westreich, Thea (San Francisco : San Francisco Museum of Modern Art, 1999)
Acconci, Vito ; Ahtila, Eija-Liisa ; Almond, Darren ; Barney, Matthew ; Baumgarten, Lothar ; Birnbaum, Dara ; Broodthaers, Marcel ; Bruch, Klaus vom ; Clark, Larry ; Coleman, James ; Douglas, Stan ; Gilbert & George ; Graham, Dan ; Hill, Gary ; McQueen, Steve ; Mori, Mariko ; Mucha, Reinhard ; Nauman, Bruce ; Smith, Stephanie ; Stewart, Edward ; Struth, Thomas ; Tyson, Keith ; Viola, Bill ; Wall, Jeff ; Wilson, Jane & Louise
Seeing Time : Selections from the Pamela and Richard Kramlich Collection of Media Art, San Francisco Museum of Modern Art, San Francisco, October 15, 1999 to January 9, 2000
Engels
boek